Web-based 3D visualization framework for time-varying and large-volume oceanic forecasting data using open-source technologies. (January 2021) - Qin, Rufu; Feng, Bin; Xu, Zhounan; Zhou, Yusheng; Liu, Lixin; Li, Yineng
Abstract: There are limitations to traditional visualization solutions regarding real-time 3D visualization of time-varying and large-volume 3D gridded oceanographic data in a web environment. We adopted the open-source visualization technologies to implement a browser-based 3D visualization framework. The developed 3D visualization interfaces provide users 3DGIS experiences on a virtual globe and simultaneously provide efficient 3D volume rendering and enriched interactive volume analysis. Our experiments suggest that the well-designed Cesium and Plotly.js API allow researchers to easily establish 3D visualization applications while avoiding the requirements of intensive programming and computations. The case study conducted shows that the proposed methods is a feasible alternative web-based 3D visualization solution, which provides a faster rendering speed, high visual effects and on-the-fly 3D visualization of oceanographic data. Due to its open-source architecture and the simplicity of the adopted technologies, the visualization framework can be easily customized to visualize other scientific data with few modifications. Highlights: A web-based 3D visualization framework for visual analysis of oceanic forecasting data is presented. Oceanic forecasting data can be effectively displayed in a virtual globe using heatmap and moving-particle technologies. The Plotly.js enables the high-performance volume rendering and interactive analysis of large amounts of volumetric data. The visualization framework can be easily customized or adapted to display other scientific data.